The Effects of L Carnitine on in Vitro Maturation of Immature Bovine Oocytes - Nada Mohsen; Aya Megahed; AbdelRouf Hegab; Wael Eldomany; Ahmed Monir; Mohammed A Elmetwally (Journal of Veterinary Healthcare, 2025)
L-Carnitine (Lc) acts as an antioxidant that neutralizes free radicals, especially superoxide anions and protects cells against oxidative damage-induced apoptosis, as following ovulation, intracellular reactive oxygen species (ROS) accumulation increases in oocytes, Oocytes exhibit an intracellular defense mechanism against an oxidative attack. This outcome adversely affects fertilization and subsequent embryonic development, thereby increasing the risk of an early miscarriage and abnormal development of offspring. The purpose of this study was to see how adding LC to either maturation or fertilization medium affected the developmental competence of immature bovine oocytes. In this study, Ovaries from apparently normal reproductive organs of cattle were collected within 30 minutes from slaughter and evisceration of animals. Cumulus oocyte complexes (COCs) were collected by aspiration of medium sized ovarian follicles (4-8 mm). COCs of acceptable quality were selected, washed and incubated in tissue culture media 199 (TCM199) supplemented with 10% heat inactivated fetal calf serum, 5 μg/ml luteinizing hormone (LH), 0.5 μg/ml follicle stimulating hormone (FSH) and 1 μg/ml estradiol-17β for 20:22 hour at 38.5 C◦ under 5% CO2 in air with 90% humidity. different concentrations of LC (1.25,2.5 and 5mM) were used. The results were consistent for both maturation and fertilization and there is a significant increase in maturation, fertilization., cleavage and blastocyst rate. In conclusion, LC has important role in IVEP through addition of LC to maturation media or culture media it improved nuclear maturation and blastocyst formation rates in bovine oocytes.
Keywords: Bovine